Sarcoma classification by DNA methylation profiling - Kölsche, Christian; Schrimpf, Daniel; Stichel, Damian; Sill, Martin; Sahm, Felix; Reuss, David; Jones, Barbara Christine; Heilig, Christoph E.; Horak, Peter; Stark, Sebastian; Johann, Pascal-David; Selt, Florian; et al. (Nature Communications, 2021)
Sarcomas are malignant soft tissue and bone tumours affecting adults, adolescents and children. They represent a morphologically heterogeneous class of tumours and some entities lack defining histopathological features. Therefore, the diagnosis of sarcomas is burdened with a high inter-observer variability and misclassification rate. Here, we demonstrate classification of soft tissue and bone tumours using a machine learning classifier algorithm based on array-generated DNA methylation data. This sarcoma classifier is trained using a dataset of 1077 methylation profiles from comprehensively pre-characterized cases comprising 62 tumour methylation classes constituting a broad range of soft tissue and bone sarcoma subtypes across the entire age spectrum. The performance is validated in a cohort of 428 sarcomatous tumours, of which 322 cases were classified by the sarcoma classifier. Our results demonstrate the potential of the DNA methylation-based sarcoma classification for research and future diagnostic applications.